Caffeine prevents restenosis and inhibits vascular smooth muscle cell proliferation through the induction of autophagy. Issue 9 (2nd September 2022) - Tripathi, Madhulika; Singh, Brijesh Kumar; Liehn, Elisa A.; Lim, Sheau Yng; Tikno, Keziah; Castano-Mayan, David; Rattanasopa, Chutima; Nilcham, Pakhwan; Abdul Ghani, Siti Aishah Binte; Wu, Zihao; Azhar, Syaza Hazwany; Zhou, Jin; et al.
ABSTRACT: Caffeine is among the most highly consumed substances worldwide, and it has been associated with decreased cardiovascular risk. Although caffeine has been shown to inhibit the proliferation of vascular smooth muscle cells (VSMCs), the mechanism underlying this effect is unknown. Here, we demonstrated that caffeine decreased VSMC proliferation and induced macroautophagy/autophagy in an in vivo vascular injury model of restenosis. Furthermore, we studied the effects of caffeine in primary human and mouse aortic VSMCs and immortalized mouse aortic VSMCs. Caffeine decreased cell proliferation, and induced autophagy flux via inhibition of MTOR signaling in these cells. Genetic deletion of the key autophagy gene Atg5, and the Sqstm1 / p62 gene encoding a receptor protein, showed that the anti-proliferative effect by caffeine was dependent upon autophagy. Interestingly, caffeine also decreased WNT-signaling and the expression of two WNT target genes, Axin2 and Ccnd1 (cyclin D1). This effect was mediated by autophagic degradation of a key member of the WNT signaling cascade, DVL2, by caffeine to decrease WNT signaling and cell proliferation. SQSTM1/p62, MAP1LC3B-II and DVL2 were also shown to interact with each other, and the overexpression of DVL2 counteracted the inhibition of cell proliferation by caffeine. Taken together, our in vivo and in vitro findings demonstrated that caffeine reduced VSMC proliferation by inhibiting WNT signaling via stimulation of autophagy, thus reducing the vascular restenosis. Our findings suggest that caffeine and other autophagy-inducing drugs may represent novel cardiovascular therapeutic tools to protect against restenosis after angioplasty and/or stent placement.